2011
DOI: 10.1111/j.1365-313x.2011.04822.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression and manipulation of PHOSPHOENOLPYRUVATE CARBOXYKINASE 1 identifies a role for malate metabolism in stomatal closure

Abstract: SUMMARYMalate, along with potassium and chloride ions, is an important solute for maintaining turgor pressure during stomatal opening. Although malate is exported from guard cells during stomatal closure, there is controversy as to whether malate is also metabolised. We provide evidence that phosphoenolpyruvate carboxykinase (PEPCK), an enzyme involved in malate metabolism and gluconeogenesis, is necessary for full stomatal closure in the dark. Analysis of the Arabidopsis PCK1 gene promoter indicated that this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
58
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(62 citation statements)
references
References 39 publications
1
58
1
Order By: Relevance
“…NADP-ME also is expressed in Arabidopsis guard cells (Wheeler et al, 2005) and was implicated in the mechanism of stomatal closure when NADP-ME was overexpressed in tobacco (Nicotiana tabacum) plants (Laporte et al, 2002). Thus, a role for PEPCK was nearly forgotten until Penfield et al (2012) revisited the importance of this metabolic step by taking advantage of an Arabidopsis mutant lacking PEPCK1, a highly expressed guard cell isoform in this plant. The pck1 mutants have increased stomatal conductance and wider stomatal aperture than wild-type plants, pointing toward a function for PCK1 in full stomatal closure in the dark (Penfield et al, 2012).…”
Section: Synthesis Of Malate and Its Catabolism In Guard Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…NADP-ME also is expressed in Arabidopsis guard cells (Wheeler et al, 2005) and was implicated in the mechanism of stomatal closure when NADP-ME was overexpressed in tobacco (Nicotiana tabacum) plants (Laporte et al, 2002). Thus, a role for PEPCK was nearly forgotten until Penfield et al (2012) revisited the importance of this metabolic step by taking advantage of an Arabidopsis mutant lacking PEPCK1, a highly expressed guard cell isoform in this plant. The pck1 mutants have increased stomatal conductance and wider stomatal aperture than wild-type plants, pointing toward a function for PCK1 in full stomatal closure in the dark (Penfield et al, 2012).…”
Section: Synthesis Of Malate and Its Catabolism In Guard Cellsmentioning
confidence: 99%
“…Thus, a role for PEPCK was nearly forgotten until Penfield et al (2012) revisited the importance of this metabolic step by taking advantage of an Arabidopsis mutant lacking PEPCK1, a highly expressed guard cell isoform in this plant. The pck1 mutants have increased stomatal conductance and wider stomatal aperture than wild-type plants, pointing toward a function for PCK1 in full stomatal closure in the dark (Penfield et al, 2012). Furthermore, pck1 mutants close their stomata normally in response to ABA or high [CO 2 ], supporting previous observations that malate export may be more important than malate metabolism when stomata lose turgor within minutes.…”
Section: Synthesis Of Malate and Its Catabolism In Guard Cellsmentioning
confidence: 99%
“…Indeed, it has been shown that this metabolite can act as a counter-ion of K + in the vacuole of guard cells or as a signaling molecule to activate guard cell vacuolar chloride channels during stomatal opening (Hedrich and Marten, 1993;De Angeli et al, 2013). Further evidence for the importance of malate and their products and precursors for guard cell metabolism and stomatal movements is demonstrated by the higher g s found in transgenic plants for enzymes related to organic acid metabolism (Laporte et al, 2002;Nunes-Nesi et al, 2007;Araújo et al, 2011b;Penfield et al, 2012) or guard cell malate transporters (Meyer et al, 2010;Medeiros et al, 2015). The findings of these works are reflected across our entire data compilation, which revealed a strong and positive correlation between the levels of malate and g s ( Fig.…”
Section: Stomatal Conductance and Primary Metabolism: The Role Of Orgmentioning
confidence: 99%
“…This finding led to follow-up work demonstrating that the level of malate played an important role in tomato fruit ripening influencing starch accumulation, total soluble solid levels at ripening, and postharvest properties (Centeno et al, 2011), when taken alongside the results of many recent studies on the control of stomatal aperture by malate (NunesNesi et al, 2007;Lee et al, 2008;Araújo et al, 2011;Penfield et al, 2012), thus expanding the documented biological roles for this acid beyond those previously documented (Fernie and Martinoia, 2009;Meyer et al, 2010). This finding thus suggests that malate metabolism may exert a key influence on the normal ripening and metabolism of tomato fruit.…”
mentioning
confidence: 99%